El alfabeto fonético internacional en la comprensión y expresión fonológica en inglés en estudiantes del nivel intermedio superior del Instituto Cultural Peruano Norteamericano de Iquitos 2024 - Vargas Hemeryth, Augusto (2025)
The research aims to explain the influence of the International Phonetic Alphabet (IPA) on phonological comprehension and expression in English among upper intermediate students at the Instituto Cultural Peruano Norteamericano (ICPNA) in Iquitos in 2024. The study is explanatory, seeking to determine the impact of the IPA on phonological comprehension and expression in English within the study population, which consists of 61 students from the ICPNA Iquitos. To assess the students' knowledge of the IPA, questionnaires were used that address both the vowel and consonant dimensions of the IPA. To evaluate phonological comprehension and expression in English, a phonological comprehension test and a phonological expression test were administered. The scores from both tests were averaged. The results indicate a normal distribution of data, leading to the use of Pearson's r and linear regression with a p-value of 0,013 < 0,05, which leads to rejecting the null hypothesis and accepting the alternative hypothesis. Thus, it is concluded that the International Phonetic Alphabet does significantly influence phonological comprehension and expression in English among upper-intermediate students at the Instituto Cultural Peruano Norteamericano in Iquitos in 2024.